Analysis of the Influence of Corporate Governance Quality, Auditor Reputation, and Board Independence on the Financial Reporting Quality of Property Companies in Indonesia - Nenny Syahrenny (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The goal of this study is to show how the three factors of corporate governance quality, auditor reputation, and board independence determine the financial reporting quality of Indonesian property companies. Quality of financial reporting made the property industry, which is capital-intensive and very complicated, transparent and trustworthy in the eyes of the market; this was the point of the present research. A quantitative explanatory method was adopted by the researchers, and the secondary data used was from the financials and annual reports of property firms listed on the Indonesia Stock Exchange. The population of the research was determined through purposive sampling and multiple linear regression analysis was then performed. The findings suggest that corporate governance quality, auditor’s reputation, and board independence significantly and positively affect financial reporting quality. The present study makes a theoretical contribution, thus enriching the literature on accounting and corporate governance concerning the determinants of financial reporting quality. On the practical side, the outcomes of this research act as a compass for the management of companies, auditors, and regulators, in their endeavours to enhance the quality of financial reports and the trust of stakeholders in Indonesian property companies.